Impaired left ventricular diastolic filling in patients with familial amyloid polyneuropathy: a pulsed Doppler echocardiographic study. Issue 2 (February 1989) - Kinoshita, O; Hongo, M; Yamada, H; Misawa, T; Kono, J; Okubo, S; Ikeda, S
Abstract : To assess left ventricular diastolic filling in patients with amyloid heart disease 12 patients with familial amyloid polyneuropathy and 15 normal subjects were studied by pulsed Doppler echocardiography. None of the patients had clinical evidence of overt heart disease or restrictive cardiomyopathy and only two of them showed ventricular wall thickening. The peak flow velocity of rapid diastolic filling and the acceleration rate of early diastolic inflow were significantly lower in patients with familial amyloid polyneuropathy than in controls. The pressure half time was significantly longer in patients than in controls. In addition, the peak flow velocity during atrial contraction and the ratio of atrial peak flow velocity to rapid diastolic peak flow velocity were significantly greater in patients than in controls. Although there were no significant correlations between measurements of diastolic filling and clinical findings in patients with familial amyloid polyneuropathy, the ratio of atrial peak flow velocity to rapid diastolic peak flow velocity was significantly related to left ventricular posterior wall thickness. These findings suggest that in patients with cardiac amyloidosis without restrictive cardiomyopathy, abnormal left ventricular diastolic filling, manifested by a reduction in the rate and volume of rapid diastolic filling with enhanced atrial contraction, can be seen even in the early stage of the disease.